ANALISIS MANAJEMEN BISNIS SYARIAH PENGARUH PEMBERIAN INSENTIF, KOMPETENSI, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. TELKOM AKSES BOGOR - Fajriastuti, Virda; Trihantana, Rully; Suryani, Ermi (Sahid Business Journal : Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2024)
This study aims to determine the effect of incentives, competence, and work environment on the performance of employees of PT Telkom Access Bogor. The research method used is quantitative method. Data obtained from Google Forms. So this study set a sample of 127 people with probability sampling technique. To test the level of reliability using Croncbach's Alpha. With a significant level of 5%. The research used SPSS Version 24 tool. From the results of this study, it is seen partially with the t-test that incentives have a positive and significant effect on employee performance with tcount of 3.782 <1.657. Then competence has a positive and significant effect on employee performance with tcount of 3.225 > 1.657 and the work environment has a positive and significant effect on employee performance with tcount of 3.155 > ttable 1.657. Furthermore, the simultaneous effect test with the F test shows that the provision of incentives, competence and work environment simultaneously affects employee performance with an Fcount of 46.579 > 3.07.